Dual-Brain Psychology: A novel theory and treatment based on cerebral laterality and psychopathology - Schiffer, Fredric (Frontiers in Psychology, 2022)
Dual-Brain Psychology is a theory and its clinical applications that come out of the author's clinical observations and from the Split-brain Studies. The theory posits based on decades of rigorous, peer-reviewed experiments and clinical reports that, in most patients, one brain's cerebral hemisphere (either left or right) when stimulated by simple lateral visual field stimulation, or unilateral transcranial photobiomodulation, reveals a dramatic change in personality such that stimulating one hemisphere evokes, as a trait, a personality that is more childlike and more presently affected by childhood maltreatments that are usually not presently appreciated but are the proximal cause of the patient's symptoms. The personality associated with the other hemisphere is much more mature, less affected by the traumas, and less symptomatic. The theory can be applied to in-depth psychotherapy in which the focus is on helping the troubled side to bear and process the traumas with the help of the therapist and the healthier personality. A person's symptoms can be evoked to aid the psychotherapy with hemispheric stimulation and the relationship between the dual personalities can be transformed from conflicted and sabotaging to cooperating toward overall health. Stimulating the positive hemisphere in the majority of therapy patients rapidly relieves symptoms such as anxiety, depression, or substance cravings. Two randomized controlled trials used unilateral transcranial photobiomodulation to the positive hemisphere as a stand-alone treatment for opioid cravings and both revealed high effect sizes. The theory is supported by brain imaging and rTMS studies. It is the first psychological theory and application that comes out of and is supported by rigorous peer-reviewed experimentation.